Hubungan Tingkat Stres dengan Kejadian Nyeri Neuropati Diabetik pada Pasien Dm Tipe 2 Di RS Bhayangkara Watukosek - Dewangga, Eka Wahyu; Andiani, Andiani (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2023)
Introduction: Therapy for diabetic neuropathy pain has not been able to provide a significant effect for patients so that the side effects of pain complaints affect the quality of work and social life of type 2 DM patients at Bhayangkara Watukosek Hospital. The aim of this study was to determine whether stress levels can influence the incidence of diabetic neuropathy pain at Bhayangkara Watukosek Hospital. Method: The research is analytical in nature with Odds Ratio (OR) calculations to test hypotheses. The research population was 250 type 2 DM patients with a sample of 40 respondents taken at simple random. The variables consist of the incidence of diabetic neuropathy pain as the dependent variable, and stress level as the independent variable. Result: the relationship between stress levels and the incidence of NND in type 2 DM patients at Bhayangkara Watukosek Hospital produced an odds ratio of 3 (OR > 1). Conclusion: respondents who experienced stress were 3 times more likely to experience NND than respondents who were not stressed. To reduce or suppress the incidence of NND, people who suffer from type 2 DM and are aged ≥50 years should have regular check-ups at the hospital to prevent NND. For the management of Bhayangkara Watukosek Hospital, it is recommended to carry out a mentoring program for type 2 DM patients who are ≥50 years old because many respondents who suffer from NND and experience stress are ≥50 years old.